Department of Human Sciences, Campus III UNEB: A territory of identities - dos Santos Reis, Edmerson; Pereira dos Santos, Elenice (Guará Journal, 2023)
This article seeks to uncover proposals for consolidating actions based on the precepts of Contextualized Education for Coexistence with the Brazilian Semiarid Region (ECSAB) through development initiatives developed by the Department of Human Sciences, Campus III, of the State University of Bahia. These initiatives instigate epistemological transgression capable of fostering changes for the construction of new knowledge based on the policy of coexistence, culture, and diversity of the social subjects of the Brazilian Semiarid Region. It describes the powerful representation of Teaching, Research, and Extension projects in the formative, academic, and professional trajectories of future teachers, enabling effective action in scientific and educational processes as fields of reference and preparation for professional practice. It reveals the actions of the Extension Project Reflection of Theoretical and Practical References of Contextualized Education, which operates in an inter-multidisciplinary and transdisciplinary and contextualized manner to strengthen ECSAB’s actions within the Sertão do São Francisco region. It brings as reflective discussions conceptions about a territory of identity and its insertion in the social context as a source of cultural symbolic meanings constructed collectively, a space in which the perspective of contextualizing knowledge and understanding is the starting point of the project’s approaches.